Trends in asymptomatic STI among HIV-positive MSM and lessons for systematic screening. - Eric Farfour (Public Library of Science (PLoS), 2021)
The burden of STIs is particularly high in HIV-infected MSM patients. A recent increase in STIs prevalence has been noticed in the US and western European countries. We aim to assess trends in asymptomatic STIs following the publication of recommendations for STIs screening, i.e. Chlamydia (CT) and gonorrhea (NG). Seventeen centers located in the Paris area participated in the study. All asymptomatic HIV-infected MSM patients attending a follow up consultation were proposed to participated in the study. Asymptomatic patients were included over 2 periods: period 1 from April to December 2015 and period 2 from September to December 2017. Etiologic diagnosis of STIs including hepatitis B, C, syphilis, was performed using a serological test, including a non-treponemal titer with a confirmatory treponemal assay for syphilis. CT and NG were screened using a nucleic acid amplification test (NAATs) on 3 anatomical sites, i.e. urine, rectal and pharyngeal. Overall, 781 patients were included: 490 and 291 in periods 1 and 2 respectively. Asymptomatic CT, NG, and syphilis were diagnosed in 7.5%, 4.8% and, 4.2% respectively. The rate of patients having a multisite asymptomatic infection was 10.2% and 21.1% for CT and NG respectively. The most frequently involved anatomical sites for CT and NG asymptomatic infections were anorectal (66.1% and 55.2% respectively) and pharyngeal (47.4% and 60.5% respectively). CT and NG asymptomatic infection increased by 1.3- and 2-fold respectively between the two periods while syphilis decreased by 3 folds. Our results encourage to reconsider multisite screening for CT and NG in asymptomatic HIV positive MSM as the yield of screening urinary samples only might be low. Despite the more systematic STI screening of asymptomatic HIV positive MSM the prevalence of STI is increasing in MSM in France. Therefore, this strategy has not led to alter CT and NG transmission. The decrease of syphilis might involve self-medication by doxycycline, and the intensification of syphilis screening.